DESIGNING AND BUILDING APPLICATIONS FOR ORDERING DELIVERY OF GOODS AND LOGISTICS TO CUSTOMERS BASED ON ANDROID and WEBSITE ON NINJA XPRESS - Defri Abdul Majid Nasution; Rio Septian Hardinata; Muhammad Syahputra Novelan (Sean Institute, 2022)
Delivery of goods is very often done every day. Customers who want to send goods to other places must deliver the goods to the place of delivery. Ninja Xpress is one of the shipping agents in Indonesia. The author designs and builds a system that can place orders for delivery of goods through the Android application. This order can be made at home so that customers do not need to come to the place of delivery of goods. Applications can make delivery orders to the delivery party. The goods will be picked up at the customer's house and the specifications related to the goods will be recorded. This system is very good for customers to use so they don't have to come directly to the place of delivery..goods, delivery, information system, express